Removing Phosphate from aquatic environments utilizing Fe-Co/Chitosan modified nanoparticles - Tadeh, Issaian (2021)
Phosphorus plays a key role in cellular mechanisms and ecosystems. It is typically found inrocks and mineral deposits although it is a limited resource. Through erosion, phosphate ions aregradually released and their solubility in water presentsproblems for aquatic ecosystems. One of the problemsthat high phosphate concentrations in aquatic ecosystems cause is eutrophication. Typical phosphate concentrations in unpolluted freshwater systems canrange from 0.01 mg/L to 0.025 mg/L, howeverCorpoboyacá has found phosphate levels rangingbetween 0.801 and 11.0 mg/L. A combination ofmagnetic nanoparticles and polysaccharides (chitosan)are linked together to form chitosan modified nanoparticles (CMNPs) with the ability to performmultiple adsorption/desorption cycles with greatefficiency.